The Patent System During Global Pandemic and the Access to Medications and Vaccines - Fatou Diagne Mbaye; Agus Sardjono (Faculty of Law, Sriwijaya University, Indonesia, 2022)
The Declaration on Trade-Related Intellectual Property Rights (TRIPS) and Public Health Agreements want to promote the balanced interpretation and implementation of its provisions and promote universal access by assisting WTO members to protect public health rights. Two years will soon pass, and the emergence of new variants of COVID-19 shows that the virus will not stop at national borders. However, vaccines are gradually entering and almost monopolised by industrialised countries. If Jonas Salk thought in the 1950s that patenting his polio vaccine was like patenting the sun, the problem appearing is that today's patent holders do not think so. The COVID-19 vaccine is owned by biotech companies, universities, research institutes or pharmaceutical companies. The purpose of this research is to analyse, through a normative juridical approach, the requirement for patent holders to protect their intellectual property rights if they are to remain competitive in the marketplace. Not to forget that they must pay patent fees as a percentage of the final price of the vaccine, which is a significant benefit to the economies of the countries where they are located. While for developing countries, the best solution would be to produce their vaccines. With industrial property rights, it seems impossible to transfer the vaccine technology on COVID-19. That is why some developing countries (South Africa and India have the support of many other developing countries) have filed a complaint with the WTO, requesting a waiver of property rights under Article 31 of TRIPS in order to produce a COVID-19 vaccine on a large scale and at an affordable price.